Cross-national invariance of the entrepreneurial orientation scale - Hansen, John D.; Deitz, George D.; Tokman, Mert; Marino, Louis D.; Weaver, K. Mark (Journal of Business Venturing, 2011)
This study utilizes data from 1279 SMEs spanning seven countries to assess the cross-national invariance of the Covin and Slevin entrepreneurial orientation scale. We first examine the psychometric properties of the scale across the full sample and each of the individual countries, identifying the optimal model for invariance testing. We then conduct a series of tests for invariance, utilizing the American sample as a reference in each. Study results highlight the optimality of a three-factor, six-item scale, and provide additional information regarding the level of measurement equivalence that exists between the U.S. and each of the other countries analyzed.